Income convergence of the Western Balkan States on their path to accession to the European Union - Milutinović, Sonja; Stanišić, Tanja; Radivojević, Vladimir (Industrija, 2022)
The common and main strategic goal of all Western Balkan States is integration into the European Union. Therefore, the transition of the Western Balkan region, as was the case with other Central European transition countries, must be seen as a part of the European integration process. The aim of this research is to tests whether income convergence exists between Western Balkan States and the developed European Union countries, with a comparison with New Member States. In order to test this assumption, regression analysis is used. The results did not confirm the existence of income convergence in the entire observed period (1995-2019). However, the results indicate a strong impact of the Global Economic Crisis on income convergence, so it existed in the years before and after the Global Economic Crisis. Results also showed faster growth of the New Member States than the Western Balkan States.